OPTIMIZATION OF THE ENTERPRISE CAPITAL STRUCTURE - I. I. Chvankova (Литьë и металлургия)
The main attention is focused on efficiency of investment  of fixed and circulating assets, to what extent their correlation is optimal for financial stability of the enterprise and for choice of enterprise strategy.